2022
DOI: 10.1021/acs.nanolett.2c00361
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Water in the Tribological Behavior of Graphene in an Electric Field

Abstract: Friction properties in the electric field are important for the application of graphene as a solid lubricant in graphene-based micro/nanoelectromechanical systems. The studies based on conductive atomic force microscopy show that interfacial water between graphene and the SiO2/Si substrate affects the friction of graphene in the electric field. Friction without applying voltage remains low because the interfacial water retains a stable ice-like network. However, friction after applying voltage increases becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Owing to its two-dimensional (2D) planar structure with strong in-plane covalent bonding, graphene has an ultrahigh mechanical strength and intrinsically low surface friction. Moreover, it has been shown that the frictional properties of graphene can be actively altered by introducing topological defects, chemical functionalization, varying the supporting substrates, changing the ambient conditions like humidity and temperature, and the electronic method. These unique characteristics render graphene a promising candidate as a versatile friction modifier with atomically thin thickness. Despite the high potential, the friction regulation methods for graphene are typically irreversible, which means that its frictional property is hard to be recovered once changed.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its two-dimensional (2D) planar structure with strong in-plane covalent bonding, graphene has an ultrahigh mechanical strength and intrinsically low surface friction. Moreover, it has been shown that the frictional properties of graphene can be actively altered by introducing topological defects, chemical functionalization, varying the supporting substrates, changing the ambient conditions like humidity and temperature, and the electronic method. These unique characteristics render graphene a promising candidate as a versatile friction modifier with atomically thin thickness. Despite the high potential, the friction regulation methods for graphene are typically irreversible, which means that its frictional property is hard to be recovered once changed.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-section profile in Figure c verifies a thickness of ∼0.91 nm, which can be attributed to a GO monolayer. , The X-ray photoelectron spectroscopy (XPS) spectra in Figure e and Figure S2 indicate that the GO surface is terminated with hydrophilic groups, such as −OH and −COOH . These terminations are prone to adsorb water molecules from the atmosphere, thus resulting in a slightly larger thickness compared to the measured lattice spacing of ∼0.78 nm. Based on these results, the atomic structure of a GO monolayer is schematically depicted in Figure f. …”
Section: Resultsmentioning
confidence: 82%
“…The real part (ε′) (Equation S3, Supporting Information) and imaginary part (ε′′) (Equation S4, Supporting Information) of complex permittivity correspond to the storage and dissipation of electrical energy, respectively. [40][41][42][43] The lowest permittivity of CF and CNCs/CF at 600 °C annealing is due to the formation of carbon skeletons with poor conductivity at a lower carbonization temperature (Figures S8 and S9, Supporting Information). As the carbonization temperature increases, higher conductivity and permittivity are obtained.…”
Section: High-efficiency Ma Performancementioning
confidence: 99%